Microcontroller-Based Gas Detection in Transformer Oil - Nurmaisinta Harahap; Kartika Kartika (International Journal of Engineering, Science and Information Technology, 2022)
The transformer is one of the essential parts of an electric power system. The distribution transformer is a part of the electric power system which plays a vital role in providing electrical energy services to customers. The increasing population and the development of the times make the need for continuous electrical energy. One of the causes of insulation failure in transformers is overheating in the central part. The transformer requires a cooling system to control the heat energy generated. Transformer oil is an insulating and cooling medium for the central part of the transformer. At the time of operation, some disturbances cause the emergence of gases such as carbon dioxide, ethane, and ethylene. The purpose of this study was to design a device for detecting levels of carbon dioxide (CO2), ethane (C2H6), and ethylene (C2H4) dissolved in transformer oil by displaying the ppm (parts per million) value for each gas. Atmega328 microcontroller is used for system control and as a data processor. The data is in the form of a voltage that the ADC microcontroller feature will change. This information is used to calculate the ppm value for each gas. The concentration of this gas will be displayed on the LCD control panel. From the results of this study, the DS18B20 sensor used has an error of 0.00315%, the MG-811 sensor has an error of 10,022, the MQ-6 sensor has an error of 7,918, and the MQ-2 sensor has an error of 9,356. This is indicated by the LCD output, which receives data automatically.